Costs and Treatment Patterns Among Patients with Atopic Dermatitis Using Advanced Therapies in the United States: Analysis of a Retrospective Claims Database - Lawrence F. Eichenfield; Marco DiBonaventura; Jason Xenakis; Marie-Helene Lafeuille; Mei Sheng Duh; Iman Fakih; Mark Levenberg; Joseph C. Cappelleri; Vanja Sikirica (Adis, Springer Healthcare, 2020)
Abstract Introduction For many, atopic dermatitis (AD) is not adequately controlled with topical regimens. This analysis examined treatment using advanced therapies and associated costs. Methods The IQVIA Health Plan Claims data set was analyzed. Patients aged ≥ 12 years with AD who newly initiated advanced therapy after the availability of dupilumab (March 28, 2017) and had ≥ 6 months continuous enrollment before and after their first advanced therapy claim (index date) were included. Advanced therapies included dupilumab, systemic corticosteroids (SCSs), systemic immunosuppressants (SISs), and phototherapy. A multivariate regression model was used to predict annualized follow-up healthcare costs. Results In total, 1980 patients were included (61.1% female; mean age, 41.2 years [SD, 17.4]; 11.3% < 18 years). Pre-index date, 65.2% of patients used topical corticosteroids (TCSs; 40.7% and 32.1% used medium and high potency, respectively). The most common advanced therapy was SCSs (N = 1453 [73.4%]; 69.2% prednisone) followed by dupilumab (N = 265 [13.4%]), SISs (N = 99 [5.0%]; 47.5% methotrexate), and phototherapy (N = 163 [8.2%]). Of patients treated with dupilumab, SISs, and phototherapy, 17.4%, 26.3%, and 14.1%, respectively, were prescribed SCSs post-index date. Overall, 62.6% of patients initiating SCSs, 49.1% initiating dupilumab, 64.6% initiating SISs, and 36.2% initiating phototherapy were prescribed TCSs post-index date. Mean annualized total costs (SD) post-index date were $20,722 ($47,014): $11,196 ($41,549) in medical costs ($7973 [$35,133] in outpatient visit costs) and $9526 ($21,612) in pharmacy costs. Mean annualized total cost (SD) varied significantly (P < 0.05) by index treatment: dupilumab, $36,505 ($14,028); SCSs, $17,924 ($49,019); SISs, $24,762 ($47,583); phototherapy, and $17,549 ($57,238). Conclusions Switching to combination therapy with SCSs and TCSs was common within 6 months of initiating advanced therapy in patients with AD. Patients also incurred significant pharmacy and outpatient costs. These results highlight the difficulty of managing AD with these existing treatment options.